Dielectronic recombination of ground-state and metastable Li+ ions - Saghiri, Amir Ahmad; Linkemann, J.; Schmitt, M.; Schwalm, Dirk; Wolf, Andreas; Bartsch, T.; Hoffknecht, A.; Müller, A.; Graham, W. G.; Price, A. D.; Badnell, N. R.; Gorczyca, T. W.; et al. (Physical review. A, Atomic, molecular, and optical physics, 1999)
Dielectronic recombination has been investigated for Δn=1 resonances of ground-state Li+(1s2) and for Δn=0 resonances of metastable Li+(1s2s3S). The ground-state spectrum shows three prominent transitions between 53 and 64 eV, while the metastable spectrum exhibits many transitions with energies <3.2 eV. Reasonably good agreement of R-matrix, LS coupling calculations with the measured recombination rate coefficient is obtained. The time dependence of the recombination rate yields a radiative lifetime of 52.2±5.0 s for the 23S level of Li+.